Colorectal Cancer Prevalence in Palembang, South Sumatera, Indonesia - Tiranda, Yulius; Safitriana, Safitriana (Universitas Ahmad Dahlan, 2018)
Background: Colorectal cancer is the third number of cancer diagnose worldwide. The incidence of this cancer is increasing year by year, particularly in developing countries. However, there is less known the number of CRC in Palembang, South Sumatera, Indonesia. Method: This study used a descriptive research design to describe the demography of epidemiology of CRC and the spread of colorectal cancer survivors in Palembang. This study used secondary data from 3 hospitals in Palembang municipality from 2013-2016. Results: The results of this study were found that the average age of CRC survivors 51,36 years which the number of CRC prevalence in a female was higher rather than male, rectal cancer was higher rather than colon cancer and the highest prevalence of this cancer is located at the sub-district of Seberang Ulu I (SU I). Conclusion: Determine the highest area of CRC could lead further action by related stakeholders on increasing healthy behavior of the community.